THE EFFECT OF FAST METHOD HEALTH EDUCATION ON FAMILY KNOWLEDGE AS AN ANTICIPATION IN HANDLING STROKE SYMPTOMS AT SUNGAI LIMAU PUBLIC HEALTH CENTER - ARINI, LARASUCI; PRASETYANINGSIH; ZALMADANI, HENDRO; YUSRA, REZKI YETI (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2025)
Hypertension is one of the factors that causes stroke. Stroke is one of the non-communicable diseases that is the leading cause of death and disability worldwide. The FAST (Face, Arms, Speech, and Times) method is one method that can be used to find out and detect stroke. Early detection of stroke with FAST is effective in accelerating the provision of interventions so as to minimize disability. This study aims to determine the effect of FAST method health education on the knowledge of families suffering from hypertension at the Sungai Limau Health Center. This type of quantitative research with a quasi-experimental design using a one group pretest posttest approach. The study was conducted on August 27, 2024. The sample consisted of 20 respondents with a total sampling technique. The instruments were in the form of questionnaires, Counseling Event Units (SAP) and leaflets. Data analysis used a paired t-test at α = 5%. The results showed that the knowledge of families suffering from hypertension before being given FAST method health education was in the poor category, namely 11 people (55%). The category of respondent knowledge became good, namely 13 people *65.0%) after being given FAST method health education. The results of the paired t-test showed a p-value = 0.000 <α = 0.05 which means that FAST method health education has an effect on the knowledge of families suffering from hypertension at the Sungai Limau Health Center. In conclusion, there is an effect of FAST method health education on the knowledge of families suffering from hypertension at the Sungai Limau Health Center. Suggestions, it is hoped that the Sungai Limau Health Center can provide regular counseling to all hypertension sufferers in this area.